2022
DOI: 10.3389/fmars.2022.964172
|View full text |Cite
|
Sign up to set email alerts
|

Examining the expansion of Spartina alterniflora in coastal wetlands using an MCE-CA-Markov model

Abstract: The spread of Spartina alterniflora (smooth cordgrass) has put biodiversity and ecosystem function at risk since it was introduced to China just a few decades ago. A better understanding of how the range of S. alterniflora will expand in the future will help manage the invasion of this species in coastal wetlands. However, it is difficult to model the future extent of Spartina saltmarshes in China. To address this issue, we combined multi criteria evaluation with traditional CA Markov model to provide robust f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Our study confirmed a negative correlation between macrophyte diversity indicators (except for the proportion of emergent vegetation) with agricultural use and urbanised areas. Increasing agricultural intensity and urbanisation in lake watersheds leads to increased nutrient delivery to the lake littoral [ 48 , 49 ]. This leads to eutrophication, which ultimately reduces lake macrophyte diversity [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed a negative correlation between macrophyte diversity indicators (except for the proportion of emergent vegetation) with agricultural use and urbanised areas. Increasing agricultural intensity and urbanisation in lake watersheds leads to increased nutrient delivery to the lake littoral [ 48 , 49 ]. This leads to eutrophication, which ultimately reduces lake macrophyte diversity [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Markov model is a spatial transformation model based on raster data and is used to predict event probabilities [51]. The state and development trend of incidents were predicted by a transition probability matrix between different time states [52].…”
Section: Landscape Pattern Prediction Modelsmentioning
confidence: 99%
“…The CA-Markov model combines the ability of CA models to simulate complex spatial variations with the strengths of Markov models in temporal prediction [54], and it has both the ability of CA models to simulate the spatial variations of complex systems and the numerical analysis capability of Markov models to predict the long-term dynamics [51]. Therefore, in this study, the CA-Markov model in IDRISI Selva software was used to simulate and predict the distribution of landscape patterns in 2030 from the land use data of each period.…”
Section: Landscape Pattern Prediction Modelsmentioning
confidence: 99%
“…We coupled CA with Markov models, and utilized the matrix of transition probabilities to model an alteration in the pattern of land cover over time, by employing the CA-Markov model, which is part of the IDRISI software package [29]. Firstly, we acquired the transition probability matrix of ground-cover type changes in the research region from 2000 to 2010, 2010 to 2015, and 2010 to 2020, by making use of the Markov module, which is included in the IDRISI program.…”
Section: Mce Ca-markovmentioning
confidence: 99%